2020
DOI: 10.1016/j.clinthera.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Comparison of Ceftazidime/Avibactam Versus Meropenem in the Empirical Treatment of Hospital-acquired Pneumonia, Including Ventilator-associated Pneumonia, in Italy

Abstract: Purpose: Ceftazidime/avibactam (CAZ-AVI) is a fixed-dose combination antibiotic approved in Europe and the United States for patients with hospitalacquired pneumonia, including ventilator-associated pneumonia (HAP/VAP). The economic benefits of a new drug such as CAZ-AVI are required to be assessed against those of available comparators, from the perspective of health care providers and payers, through cost-effectiveness and cost-utility analyses. The objective of this analysis was to compare the cost-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
8
0
2
Order By: Relevance
“…These studies found that CA was cost-effective for CRE-BSIs and -pneumonia based on accepted willingness topay-standards in both the United States (US) and Italy. 52,53 Similar conclusions were reached for low-to middle-income countries for CA versus colistin for CRE-BSIs and pneumonia in Peru. 54 Particularly relevant to South Africa, recent reports have focused on the role of CA in OXA-48-producing bacteria.…”
Section: Carbapenemase-producing Enterobacteralessupporting
confidence: 55%
See 1 more Smart Citation
“…These studies found that CA was cost-effective for CRE-BSIs and -pneumonia based on accepted willingness topay-standards in both the United States (US) and Italy. 52,53 Similar conclusions were reached for low-to middle-income countries for CA versus colistin for CRE-BSIs and pneumonia in Peru. 54 Particularly relevant to South Africa, recent reports have focused on the role of CA in OXA-48-producing bacteria.…”
Section: Carbapenemase-producing Enterobacteralessupporting
confidence: 55%
“…51 Ceftazidime-avibactam also has more favourable PK characteristics than colistin and has been shown to be better tolerated and several positive cost-effectiveness analyses have also been reported for BSIs, HAP and VAP. 52,53 Outcomes evaluated included quality-adjusted life-years, healthcare costs and incremental cost-effectiveness ratios. These studies found that CA was cost-effective for CRE-BSIs and -pneumonia based on accepted willingness topay-standards in both the United States (US) and Italy.…”
Section: Carbapenemase-producing Enterobacteralesmentioning
confidence: 99%
“…Our study only analyzed the cost-effectiveness of ceftazidime/avibactam in patients with cUTI, because antibiotics related to cIAI treatment cannot form a closed loop. Similarly, studies have been performed for bacteremia, cIAI, and hospital-acquired pneumonia/ventilator acquired pneumonia (Kongnakorn et al, 2019b;Simon et al, 2019;Tichy et al, 2020), and the pharmacoeconomics results of ceftazidime/avibactam were all favorable in these studies. The economic effects of ceftazidime/avibactam for different types of infection require more researches to confirm.…”
Section: Discussionmentioning
confidence: 76%
“…Considerando que os dados da OPAS (2020) revelam os gastos com saúde como sendo os maiores dentre todos os gastos estatais e permanecem com tendência de crescimento acelerado, levando em consideração que, nos dias atuais, esses gastos representam 10% do Produto Interno Bruto (PIB) mundial. No Brasil ele é de 8%, sendo 4,4% em gastos privados (55% do total) e 3,8% PIB são com gastos públicos (45% do total).…”
Section: Introductionunclassified
“…Da mesma forma o estudiosoVaron (2014), analisou o custo-efetividade comparando medicações estimando a eficácia da linezolina no custo da vancomicina associada a PAV por Staphylococcus aureus resistente à meticilina na Colombia, foi possível obter como resultado que na Colombia a Linezolina seria uma alternativa custoefetiva no tratamento da PAV, pela disposição de pagar mais de UU$ 5.061.173 por paciente curado.Por fim, ao realizarem um estudo de custo-efetividade para comparar o custoefetividade do CAZ-AVI versus meropenem no tratamento empírico de pacientes hospitalizados apropriados com HAP/PAV, causada por patógenos gram-negativos, sob a perspectiva de cuidados de saúde financiados publicamente na Itália, Eszter et al(2020), trazem os resultados do modelo mostrando que se espera que o CAZ-AVI forneça benefícios clínicos em pacientes hospitalizados com HAP/PAV na Itália a um custo aceitável em comparação com o meropenem.…”
unclassified